Research progress of Traditional Chinese Medicine external nursing technology in prevention and treatment of functional constipation in the elderly (中医外用护理技术防治老年功能性便秘研究进展) - WEN Mian (米文安); LI Yan (李雁); DU Danying (杜丹颖); ZHANG Haiying (张海英) (中西医结合护理)
Functional constipation has a serious impact on quality of life of elderly patients. This paper summarized the Research progress of external nursing technology of Traditional Chinese Medicine(TCM) in prevention and treatment of functional constipation in the elderly, and provided reference for clinical practice and further development of TCM external nursing technology. (老年功能性便秘严重影响患者的生活质量。本文总结了近年来中医外用护理技术防治老年功能性便秘的研究进展, 以期为临床老年功能性便秘的护理工作提供参考, 促进中医外用护理技术的发展。)